1991
DOI: 10.2134/agronj1991.00021962008300040019x
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Canopy Energy Balances of a Row Crop at Partial Cover

Abstract: When crops are grown in a row configuration, heat and mass transfer within the soil‐canopy system influence the energy and water balance of the crop. Field experiments were conducted near Lubbock, TX, to examine the energy balance of the soil and canopy separately, in cotton (Gossypium hirsutum L.) under a variety of aerial and soil moisture conditions. Bowen ratio techniques were used to obtain the field energy balance, including total latent heat flux (LE). Latent heat flux from the crop canopy (LEc was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
68
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 17 publications
24
68
1
Order By: Relevance
“…There was more exposed soil in 2008 than in 2007. The irrigated plots had a maximum of only 56% GC, with the exposed soil surface contributing to the increased canopy temperature through sensible heat transfer to the canopy and surrounding environment [5]. Development of the VITT approach for determining crop water stress was intended to account for partial crop canopy cover [6] in semi-arid regions, like the Texas High Plains.…”
Section: Surface and Air Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…There was more exposed soil in 2008 than in 2007. The irrigated plots had a maximum of only 56% GC, with the exposed soil surface contributing to the increased canopy temperature through sensible heat transfer to the canopy and surrounding environment [5]. Development of the VITT approach for determining crop water stress was intended to account for partial crop canopy cover [6] in semi-arid regions, like the Texas High Plains.…”
Section: Surface and Air Temperaturementioning
confidence: 99%
“…It is common for irrigated production systems located in arid or semi-arid regions to not reach full ground canopy cover as a result of their relatively high evapotranspiration (ET) demand and lack of sufficient irrigation. For effectively using remote sensing imagery in CWSI-based irrigation scheduling, there is a need to separate the effects of the canopy and soil spectral responses [4] and account for the significant contribution of exposed soil in the surface energy balance of the crop [5].…”
Section: Introductionmentioning
confidence: 99%
“…Latent heat fluxes from the canopy and the soil are complex processes governed by energy exchange between the soil, canopy, and the aerial environment. Investigating evaporation and energy exchanges in the crop field requires energy balance of the soil and the canopy to be examined separately (Ham et al, 1991). Several methods are used to measure or determine evapotranspiration (ET) components simultaneously.…”
Section: Combined Measurements Of Transpiration and Soil Evaporationmentioning
confidence: 99%
“…Several methods are used to measure or determine evapotranspiration (ET) components simultaneously. Ham et al (1991) showed that energy balances of canopy and soil in a cotton field could be determined by combining sap flow with BREB measurements of transpiration (T) and evapotranspiration respectively. Also, ET in a drip-irrigated vineyard was determined from separate measurements of T by sap flow gauges and soil evaporation (E s ) by micro-lysimeters at various positions (Yunusa et al, 2004).…”
Section: Combined Measurements Of Transpiration and Soil Evaporationmentioning
confidence: 99%
See 1 more Smart Citation